2019
DOI: 10.3389/fmicb.2019.00666
|View full text |Cite
|
Sign up to set email alerts
|

Akt/AS160 Signaling Pathway Inhibition Impairs Infection by Decreasing Rab14-Controlled Sphingolipids Delivery to Chlamydial Inclusions

Abstract: Chlamydia trachomatis , an obligate intracellular bacterium, intercepts different trafficking pathways of the host cell to acquire essential lipids for its survival and replication, particularly from the Golgi apparatus via a Rab14-mediated transport. Molecular mechanisms underlying how these bacteria manipulate intracellular transport are a matter of intense study. Here, we show that C. trachomatis utilizes Akt/AS160 signaling pathway to promote sphingolipids delivery to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 93 publications
(166 reference statements)
0
15
1
Order By: Relevance
“…4c). Both the MAPK and PI3K pathways activated during infection are critical for chlamydial development 5962 . Therefore, the phosphorylation status of AKT and GSK3ß was examined in HeLa 229 and human Fimb cells, which were treated with IFN-γ and/or Trp and infected with Chlamydia .…”
Section: Resultsmentioning
confidence: 99%
“…4c). Both the MAPK and PI3K pathways activated during infection are critical for chlamydial development 5962 . Therefore, the phosphorylation status of AKT and GSK3ß was examined in HeLa 229 and human Fimb cells, which were treated with IFN-γ and/or Trp and infected with Chlamydia .…”
Section: Resultsmentioning
confidence: 99%
“…SFKs at microdomains regulate inclusion trafficking along microtubules to the microtubule organization center (MTOC) and hence may hijack the vesicular transport along microtubules. A recent study found C. trachomatis utilizes the Akt/AS160 signaling pathway to acquire sphingolipids via Rab14 mediated vesicular transport [ 41 ]. Akt remains phosphorylated and recruited to the inclusion membrane for the duration of infection and is essential for chlamydial replication, inclusion size, and infectivity [ 41 ].…”
Section: Host Kinases In Nutrient Acquisition By Chlamydmentioning
confidence: 99%
“…Chlamydia directly obtain ceramide from the host cell Golgi and incorporate it into the inclusion membrane (Hackstadt et al, 1995; Figure 2). This is a process essential for the pathogen survival, in which chlamydial inclusion fuses with trans- Golgi network-derived secretory vesicles (van Ooij et al, 2000) in an Akt and Rab14-mediated way (Capmany and Damiani, 2010; Capmany et al, 2019). C. trachomatis has also been reported to cause the fragmentation of Golgi and to induce formation of mini stacks in the vicinity of the inclusion membrane, which supports lipid acquisition from the host (Heuer et al, 2009).…”
Section: Once Inside - Role Of Sphingolipids In Bacterial Reproductiomentioning
confidence: 99%